Effects of Kaempfera parviflora supplementation on the cardiovascular endurance of athletes: A randomized, placebo controlled, parallel design study - Onsiri, S.; Amitpai, C.; Sukomol, N.; Sirisopon, N.; Tanpanit, A. (Asian Journal of Sports Medicine, 2020)
Background: Kaempfera (K.) parviflora (i.e., Thai ginseng) is believed to have medicinal properties associated with good health (e.g., increased vitality, metabolism booster) because it expands blood vessels, which allows for increased blood flow. These effects might extend into the realm of improving physical performance, specifically that of the cardiovascular system.